2019
DOI: 10.3389/fgene.2019.00947
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Loci for Infant Head Circumference Identified by a Joint Association Analysis

Abstract: As an important trait at birth, infant head circumference (HC) is associated with a variety of intelligence- and mental-related conditions. Despite being dominated by genetics, the mechanism underlying the variation of HC is poorly understood. Aiming to uncover the genetic basis of HC, we performed a genome-wide joint association analysis by integrating the genome-wide association summary statistics of HC with that of its two related traits, birth length and birth weight, using a recently developed integrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…54 Previous studies have found that the genetic background of birth weight is also associated with head circumference at birth and in later life. 55,56 Altogether, the findings of the current study suggest that fetal and infant weight growth are associated with brain morphology in school-age children. Even though the observed associations are relatively small, they are important from a developmental and preventive perspective.…”
Section: Interpretation Of Main Findingssupporting
confidence: 59%
“…54 Previous studies have found that the genetic background of birth weight is also associated with head circumference at birth and in later life. 55,56 Altogether, the findings of the current study suggest that fetal and infant weight growth are associated with brain morphology in school-age children. Even though the observed associations are relatively small, they are important from a developmental and preventive perspective.…”
Section: Interpretation Of Main Findingssupporting
confidence: 59%
“…AsAoD displayed a high heritability in line with other continuous measurements of human anatomy such as height and head circumference 34 . However, genetic determinants of the aortic outflow tract size are likely under purifying selection as comparative anatomy suggests the physiological demands of cardiac output are relatively invariant across a wide range of mammalian body sizes 35 .…”
Section: Discussionmentioning
confidence: 61%
“…These findings suggest a shared genetic architecture between AsAoD and cardiovascular diseases and risk factors.Our gene level association studies identified 147 trait associations among which 19 genes were also found to be significantly enriched in multiple tissues and cell types including heart, blood vessels, and cells transformed fibroblast; highlighting a potential role of these genes in functions related to development, maintenance, or regulation of aorta structure and diameter. This finding is concordant with our tissue enrichment analysis that showed significant enrichment of GWAS signals in the aorta, arteries, heart and other predominantly smooth muscle cell tissues.AsAoD displayed a high heritability in line with other continuous measurements of human anatomy such as height and head circumference34 . However, genetic determinants of the aortic outflow tract size are likely under purifying selection as comparative anatomy suggests the physiological demands of cardiac output are relatively invariant across a wide range of mammalian body sizes35 .…”
mentioning
confidence: 58%
“…Both rs17361324 (ADCY5) and rs215226 (B4GALNT3) have enhancer and promoter histone marks and eQTLs in the respective genes in relevant tissues. For BMI, there is an eQTL for rs17361324-ADCY5 in thyroid, and ADCY5 has been previously associated with type 2 diabetes, 91 BMI, 92 central obesity traits, 43 height, 51 birth outcomes, [93][94][95] and a number of other phenotypes. Additionally, rs17361324 is proximate to an ADCY5 intronic variant (rs1093467, r²=0.3 in 1000 Genomes AMR) that is highly conserved across species (Haploreg v4.1).…”
Section: Discussionmentioning
confidence: 99%